Self‐assembling protein scaffold‐mediated enzymes' immobilization enhances in vitrod‐tagatose production from lactose. Issue 1 (16th March 2022) - Liu, Wei; Jiang, Cheng; Zhang, Yiwen; Zhu, Liying; Jiang, Ling; Huang, He
Abstract: As a rare low‐calorie sugar with special medicinal value, d ‐tagatose is widely used in the field of food, beverages, medicine, and cosmetics. However, enzymatic d ‐tagatose production in vitro is commonly limited to low conversion efficiency and poor thermo‐stability. Herein, taking advantage of the self‐assembling property of protein scaffold EutM (ethanolamine bacterial microcompartments), Spy and Snoop peptide pairs was used to drive the linkage between the EutM and cargo proteins, β‐galactosidase (BagB), and l ‐arabinose isomerase (TMAI) to construct a dual‐enzymes cascade and realize the d ‐tagatose production from lactose. The optimal conditions of the cascade were shown to be pH of 8.0, temperature of 60°C, 100 g/L lactose as substrate with supplementing 5 mM Mn 2+ . When the ratio of immobilized enzymes to EutM scaffold reached 1:6, the d ‐tagatose productivity of the dual‐enzymes cascade could reach 1.03 g/L/h, which was 1.24‐fold higher than free enzymes. In addition, the EutM‐based scaffold could efficiently improve the stability of immobilized enzymes, in which 45% of the activity remained after 12 h, 2.14‐fold higher than the free one. Overall, an attractive EutM‐based self‐assembling platform immobilizing BagB and TMAI was developed, showing enhanced catalysis efficiency and enzyme thermo‐stability for d ‐tagatose production. Abstract : An attractive EutM (ethanolamine bacterial microcompartments)‐based self‐assembling protein platform immobilizing β‐galactosidase (BagB) and l ‐arabinose isomerase (TMAI) was developed for d ‐tagatose production with enhanced catalysis efficiency and enzyme thermo‐stability; here the d ‐tagatose's productivity was increased by 1.24‐folds, and 2.14‐times higher residual activity was obtained after 12 h compared with free enzymes.